PENGUATAN KELOMPOK TERNAK MEDAL SALUYU CIRATA KABUPATEN PURWAKARTA DALAM UPAYA MENINGKATKAN KESEJAHTERAAN PETERNAK - A. Yoesdiarti, Arti; E. Yolynda; T. Sariati; F. R. Dewi (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2024)
Sheep have many advantages and have the potential to be developed because they gain profits more quickly, have lower risks, and have higher nutritional value than other livestock. Developing farmers’ groups can be a solution to increasing sheep productivity. The Medal Saluyu Farmers Group as one of the sheep breeders shows the need for assistance for the development of their group. Community service activities are carried out starting from initiation and problem mapping in April 2023 until implementation on June 16 - 17 2023. Activities carried out include counseling and training on feed management and mapping the potential for feed business development, digital marketing, administration, processing, and group dynamics. The activity was carried out at the Medal Saluyu Livestock Group in Cisalak Village RT 06 RW 03 Karoya Village, Tegalwaru District, Purwakarta. The activity involved around 15 breeders. From these activities, it was concluded that further assistance was needed to be able to develop livestock groups by involving various entities such as academics, agricultural services, practitioners in larger companies, private companies (in the context of Corporate Social Responsibility), and local government.